In de USSR en erbuiten : 28 Kunstenaars 1970-1990. - Bazjanov, L; Beeren, W.A.L.; Bertheux, Maarten; Boechoemov, Nikolai; Borovsky, Aleksandr; Erofeev, Andreï; Sassen, Jan Hein (Amsterdam : Stedelijk Museum Amsterdam, 1990)
Tselkov, Oleg ; Komar, Vitaly ; Melamid, Alexander ; Infante, Francisco ; Bulatov, Erik ; Prigov, Dmitrij ; Kabakov, Ilya ; Avvakumov, Yuri ; Plavinskij, Dmitrij ; Turetski, Boris ; Nemuchin, Vladimir ; Tschujkow, Iwan ; Lebedev, Rostislav ; Kosolapov, Aleksandr ; Sokov, Leonid ; Orlov, Boris ; Zvozdotshetov, Konstantin ; Albert, Yurij ; Panitkov, Nikolaj ; Kizeval'ter, Georgij ; Mironenko, Sergej ; Arshakuni, Zaven ; Ovchinnikov, Ilja ; Belkin, Anatoli ; Jakovlev, Vladimir I. ; Sjteijnberg, Eduard ; Abramishvill, Gia ; boegajew, sergej ; Novikov, Timur ; Olshvang, Anton ; Ovchinnikov, Vladimir ; Serp, Sergei ; Tistol, Oleg ; Volkov, Sergej ; Zakharov, Vadim ; Bezrukov, Igor ; Yufit, Yevgenii ; Kustov, Vladimir ; Morozov, Valerij
vol. 5: in de ussr en erbuiten, 16 p. : ill.
In de USSR en erbuiten : 28 Kunstenaars 1970-1990, Stedelijk Museum, Amsterdam, 22.09 - 04.11.1990
Nederlands & Engels
boek
Keywords: Rusland